1970
DOI: 10.1111/j.1476-5381.1970.tb12900.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of smooth muscle of the rat renal pelvis—response of the isolated pelvis muscle to angiotensin and some other substances

Abstract: Summary The circular component of the renal pelvis muscle of the rat appears as an intact band around the tip of the papilla. The isolated pelvis muscle strip showed spontaneous rhythmic contractions in Locke solution at 38° C. The rate of contractions corresponded with the rate of pressure fluctuations recorded during free‐flow from a ureteral catheter inserted up to the renal hilum of anaesthetized rats. Angiotensin and adrenaline (13 ng/ml) produced a rise in tone of the isolated pelvis muscle, and an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1
1

Year Published

1970
1970
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 9 publications
1
13
1
1
Order By: Relevance
“…9,35 We observed no changes in VEGF mRNA level, VEGF immunolocalization, and vascular bundle organization in two experimental rat models with postnatal polyuria and intact AngII signaling. The microvascular injury is therefore not caused by excessive urine …”
Section: Discussionmentioning
confidence: 71%
“…9,35 We observed no changes in VEGF mRNA level, VEGF immunolocalization, and vascular bundle organization in two experimental rat models with postnatal polyuria and intact AngII signaling. The microvascular injury is therefore not caused by excessive urine …”
Section: Discussionmentioning
confidence: 71%
“…It was reported by Butcer et al (1957) and Finberg and Peart (1970) that acetylcholine had little or no effect on the calyceopyeloureter system. Gruber (1928) and Deane (1967) noted enhancement of ureteral peristalsis by acetylcholine, whereas Chen et al (1957) and Borgstedt et al (1962) described that acetylcholine suppressed peristaltic movement of the ureter.…”
Section: Discussionmentioning
confidence: 84%
“…FINBERG and PEART(1970),in the experiments recording the contraction of circular muscle in the isolated pelvis,found that acetylcholine was without effect,suggesting that the acetylcholine receptor does not exist in the circular muscle of the pelvis.The fact indicates that acetylcholine receptors may exist in the longitudinal muscles,because the preparations consisting of longitudinal and circular muscles used in the present experiments respond to acetylcholine evidently.A marked decline of the sensitivity to acetylcholine by removal of the pelvic region is compatible with the fact that there is relatively rich innervation on a specific region of smooth muscles in the pelvic region (DIXON and GOSLING,1971). ELBADAWI and SCHENK(1969)and DUARTE-ESCALANTE et al(1969)showed the existence of cholinergic and adrenergic nerves along the entire length of the ureter.The latter group also pointed out that a type of concentrated neuron-like or ganglion cell has been found at the lower part of the renal pelvis and that the cholinergic innervation is better developed than the adrenergic one at the ureteropelvic junction.These facts consist with the present results that the pelvic region is different from the other part of the ureter in sensitivity to acetylcholine and that,in spite of the existence of cholinergic nerves in the upper ureter,receptors reacting to acetylcholine are extremely few as compared to the pelvic region.Accordingly,the observations in the Magnus method are consistent with findings in the intact dog by KIIL and KJEKSHUS(1966)and pelvic region,as well as the higher cholinesterase activity in the calyx-pelvis.…”
Section: Discussionmentioning
confidence: 99%